The relationship between physical activity and anxiety in college students: exploring the mediating role of lifestyle habits and dietary nutrition - Sun, Dezhuo; Zhu, Xiangfei; Bao, Zhonghan (Frontiers in Psychology, 2024)
Physical activity has been shown to be effective in treating and improving anxiety in college students.However, no studies have been conducted to examine the relationship between physical activity and anxiety in college students through mediating factors such as dietary nutrition and lifestyle habits.Therefore, the aim of this study was to examine the mediating role of lifestyle and dietary nutrition in the relationship between physical activity and anxiety.This study used a stratified random sampling method to survey 498 college students from three universities in Fujian, China.Data on participants' demographic characteristics, physical activity, lifestyle habits, and dietary nutrition were collected and analyzed using SPSS software.The proposed structural equation model was analyzed using Amos software.The results of the study showed that dietary nutrition and lifestyle habits had significant independent mediating effects and continuous multiple mediating effects (P < 0.01) in the effects of physical activity on college students' anxiety. Dietary nutrition and lifestyle habits played an independent mediating role, accounting for 24.9% of the total effect; there was also a continuous multiple mediating effect between dietary nutrition and lifestyle habits, accounting for 13.27% of the total effect value. In addition, physical activity had a direct effect value on anxiety in college students, accounting for 36.93% of the total effect value.By increasing the behavior and awareness of college students to participate in physical activity, supplemented by guiding them to develop regular lifestyle habits and correct dietary nutritional patterns, the anxiety level of college students can be effectively improved and reduced.This type of regulation is an important reference for the self-management and rehabilitation of college students with anxiety disorders.Future studies can experimentally develop a combined intervention of physical activity, lifestyle habits, and dietary nutritional